Design and Development For Stock Locator: A Case Study of FMCG Companies - Herdiana, Mochamad Rafi Herdiana; Dewi, Yulida Intan Dewi; Hernadewita, Hernadewita (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2026)
Inventory management in a finished goods warehouse often faces the challenge of quickly and accurately locating goods, which impacts operational efficiency and reduces inventory picking errors. This research aims to design a stock locator application that facilitates the real-time finding and monitoring of goods in finished goods warehouses. The methods used include user needs analysis, intuitive user interface-based system design, and web-based application development to ensure broad accessibility. In addition, the app implements an efficient location search algorithm to speed up stock searches. The application design significantly optimizes warehouse operations by replacing manual searching with precise digital navigation and route optimization, drastically reducing retrieval time. Accuracy is guaranteed through mandatory barcode validation and real-time inventory syncing, ensuring the physical stock always matches the digital record. Furthermore, it mitigates human error by eliminating manual data entry and enforcing strict, system-guided workflows that prevent incorrect picks before they occur. The application design uses a Use Case Diagram to map actors with an interest in inventory management and to define the technical design based on the functionality of the inventory management application. The design aims to avoid existing costs, such as Container Accommodation Costs or Shipping Delays. Before the implementation of this application, the total findings for 1 semester were 10 findings of existing shipping closing, after which 0 findings of existing shipping closing—the previous loss of Rp. 10,000,000 became Rp. 0. These findings make an important contribution to the application of information technology in warehouse management and open up opportunities to increase productivity through the digitization of storage and inventory sourcing processes.